Does cardiac rehabilitation meet minimum standards: an observational study using UK national audit?. Issue 1 (9th January 2017) - Doherty, Patrick; Salman, Ahmad; Furze, Gill; Dalal, Hasnain M; Harrison, Alexander
Abstract : Objective: To assess the extent by which programmes meet national minimum standards for the delivery of cardiac rehabilitation (CR) as part of the National Certification Programme for Cardiovascular Rehabilitation (NCP_CR). Methods: The analysis used UK National Audit of Cardiac Rehabilitation (NACR) data extracted and validated for the period 2013–2014 set against six NCP_CR measures deemed as important for the delivery of high-quality CR programmes. Each programme that achieved a single minimum standard was given a score of 1. The range of the scoring for meeting the minimum standards is between 1 and 6. The performance of CR programmes was categorised into three groups: high (score of 5–6), middle (scores of 3–4) and low (scores of 1–2). If a programme did not meet any of the six criteria, they were considered to have failed. Results: Data from 170 CR programmes revealed statistically significant differences among UK CR programmes. The principal findings were that, based on NCP_CR criteria, 30.6% were assessed as high performance with 45.9% as mid-level performance programmes, 18.2% were in the lower-level and 5.3% failed to meet any of the minimum criteria. Conclusions: This study shows that high levels of performance is achievable in the era of modern cardiology and that many CR programmes are close to meeting high performance standards. However, substantial variation, below the recommended minimum standards, exists throughout the UK. National certification should be seen as a positive step to ensure that patients, irrespective of where they live, are accessing quality services.